Application of Peptide Nucleic Acid-based Assays Toward Detection of Somatic Mosaicism - Christopher S Hong; Chunzhang Yang; Zhengping Zhuang (Elsevier, 2016)
Peptide nucleic acids (PNAs) are synthetic oligonucleotides with many applications. Compared with DNA, PNAs bind their complementary DNA strand with higher specificity and strength, an attribute that can make it an effective polymerase chain reaction clamp. A growing body of work has demonstrated the utility of PNAs in detecting low levels of mutant DNA, particularly in the detection of circulating mutated tumor cells in the peripheral blood. The PNA-based assay has greater sensitivity than direct sequencing and is significantly more affordable and rapid than next-generation deep sequencing. We have previously demonstrated that PNAs can successfully detect somatic mosaicism in patients with suspected disease phenotypes. In this report, we detail our methodology behind PNA design and application. We describe our protocol for optimizing the PNA for sequencing use and for determining the sensitivity of the PNA-based assay. Lastly, we discuss the potential applications of our assay for future laboratory and clinical purposes and highlight the role of PNAs in the detection of somatic mosaicism.